I was asked to solve the differential equation (solved it):

$$\left(\sqrt{xy}-\sqrt x\right)dy+ydx=0.$$

This is a separable differential equation:

$$\frac{\left(\sqrt y-1\right)dy}{-y}=\frac{dx}{\sqrt{x}}$$ assuming $x\ne 0$ and $y\ne 0$.

And the solution is:

$$2\sqrt y-\ln|y|+2\sqrt x=C.$$

The next thing I was asked to do is to check if $x=0$ or $y=0$ is a solution.

How do I check that and what does it mean? I tried plugging it in but I'm not sure I'm doing it right (I think this should not be a solution but I'm wrong).

  • $\begingroup$ The second line of your argument does not work to check if $x=0$ or $y=0$ is a solution since you are assuming $x\not=0$ and $y\not=0$ to make your differential equation separable. Is there another strategy that you can use to solve the differential equation so that you can consider the cases when $x=0$ or $y=0$? $\endgroup$ – Mee Seong Im Aug 17 '17 at 14:23
  • $\begingroup$ @MeeSeongIm I'm trying to understand the concept. when I plug the values to the original question I can see they both produce equality. but for $y=0$ I can't plug in the solution equation since $y\gt 0$ since we have $ln|y|$ but according to my book this is a solution $\endgroup$ – segevp Aug 17 '17 at 14:44
  • $\begingroup$ the solution containes the product logarithm $\endgroup$ – Dr. Sonnhard Graubner Aug 17 '17 at 14:51
  • $\begingroup$ @Cyclone according to my book it is a solution. what about $x=0$? $\endgroup$ – segevp Aug 22 '17 at 9:11

To me, the problem with writing a differential equation as a differential (i.e. $f(x,y) dx + g(x,y) dy = 0$) is that it's slightly ambiguous if you're talking about 'solutions'. In particular, a 'solution' is generally a function that depends on a variable. Where am I going with this?

To check if $y=0$ and $x=0$ are solutions, this is exactly the ambiguity you encounter. If you say `$y=0$ is a solution', you're actually talking about the function $y(x) = 0$. In that case, it's best to rewrite the differential as an ordinary differential equation for a function $y(x)$, yielding \begin{equation} \left( \sqrt{x\, y(x)} - \sqrt{x}\right) \frac{dy}{dx} + y(x) = 0.\tag{1} \end{equation} It's clear that when you substitute $y(x) = 0$ (and hence $\frac{dy}{dx} =0$), you satisfy (1). So, $y = 0$ solves the original differential equation.

Now, you can do the same with $x=0$. In this case, if you say '$x=0$ is a solution', that means that you're looking at the function $x(y) = 0$. Writing the original differential equation as an ordinary differential equation for $x(y)$ (and thus involving $\frac{dx}{dy}$) will enable you to substitute $x(y)=0$, and check whether it solves that ODE for $x(y)$.

  • $\begingroup$ thank for answering! that really helps :) $\endgroup$ – segevp Aug 22 '17 at 11:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.